2014
DOI: 10.1371/journal.pone.0099181
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Response of Platelet fV and Plasma fV to Activated Protein C and Relevance to a Model of Acute Traumatic Coagulopathy

Abstract: BackgroundAcute traumatic coagulopathy (ATC) has been linked to an increase in activated protein C (aPC) from 40 pM in healthy individuals to 175 pM. aPC exerts its activity primarily through cleavage of active coagulation factor Va (fVa). Platelets reportedly possess fVa which is more resistant to aPC cleavage than plasma fVa; this work examines the hypothesis that normal platelets are sufficient to maintain coagulation in the presence of elevated aPC.MethodsCoagulation responses of normal plasma, fV deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 71 publications
1
44
0
Order By: Relevance
“…Tissue damage and shock are associated with platelet release of soluble CD40-ligand, a potent immune activator that itself can cause further ECA and platelet activation, and is known to be necessary in order to stabilise thrombi [29]. Immune stimulation, including complement activation, is associated with release of damageassociated molecular patterns (DAMPs), such as mitochondrial DAMPs and histone-complexed DNA [30,31]. Immune activation can aggravate tissue damage through mechanisms including proteolytic degradation and oxidative stress, thus amplifying haemostatic activation.…”
Section: Immediate Effects Of Tissue Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue damage and shock are associated with platelet release of soluble CD40-ligand, a potent immune activator that itself can cause further ECA and platelet activation, and is known to be necessary in order to stabilise thrombi [29]. Immune stimulation, including complement activation, is associated with release of damageassociated molecular patterns (DAMPs), such as mitochondrial DAMPs and histone-complexed DNA [30,31]. Immune activation can aggravate tissue damage through mechanisms including proteolytic degradation and oxidative stress, thus amplifying haemostatic activation.…”
Section: Immediate Effects Of Tissue Injurymentioning
confidence: 99%
“…This mechanism is plausible but problematic due to the kinetics of the reactions. Platelets and plasma Factor Va are resistant to aPC cleavage at concentrations of aPC seen in ATC or even therapeutic use of recombinant human aPC in sepsis [31]. As a normal platelet count of 200 9 10 9 l À1 overcame aPC anticoagulant effects even at very high concentrations of aPC, and there was no detectable effect on fibrinolysis with or without platelets [31], it is difficult to envisage how aPC could drive the phenotype described as ATC.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…However the circulating concentration of PAI-1 is roughly ten times that of protein C, raising doubts about the ability of activated protein C (aPC) to deplete PAI-1 levels to the extent required to accelerate fibrinolysis (41). This has led to suggestions that ATC is a fibrinolytic form of disseminated intravascular coagulation (DIC) driven by increased tissue plasminogen activator (tPA) release from the site of injury (21,(42)(43)(44). There is also emerging evidence to implicate platelet dysfunction and endothelial glycocalyx degradation in the development of ATC (45)(46)(47)(48), although the exact contributions of these factors remains unclear.…”
Section: Intrinsic Pathway Extrinsic Pathwaymentioning
confidence: 99%
“…The protein C hypothesis therefore provides an explanation for both systemic anticoagulation and hyperfibrinolysis, although the magnitude of these effects in the development of ATC has not been quantified. (98) The significance of the protein C pathway in ATC has recently been questioned by Campbell and colleagues (44) who have shown that platelet and plasma factor Va pools are resistant to cleavage by aPC in vitro, both at concentrations observed in trauma patients and following the therapeutic doses of recombinant human aPC used in sepsis. In addition they found no evidence of fibrinolysis, arguing that the high circulating levels of PAI-1 are unlikely to be inactivated to the extent required to drive the fibrinolytic picture seen with ATC.…”
Section: Activation Of the Protein C Pathwaymentioning
confidence: 99%